Changes in pH at the dentin surface in roots obturated with calcium hydroxide pastes - Esberard, Roberta Miranda (Elsevier, 1996)
The purpose of this study was to determine the pH, after defined periods of time, in cavities prepared in the facial surface of the cervical, middle, and apical regions of roots obturated with calcium hydroxide pastes. Root canal instrumentation was performed on 40 recently extracted, single-rooted human teeth. Cavities 1.5 mm in diameter and 0.75 mm in depth were prepared in the cervical, middle, and apical regions of the facial surface of each root. Teeth were randomly divided into four groups. One group was left unobturated and served as a control. The three remaining groups were obturated with either aqueous calcium hydroxide, calcium hydroxide mixed with camphorated monochlorophenol, or Pulpdent pastes. Access cavities and apical foramina were closed with Cavit. Each tooth was stored individually in a vial containing unbuffered isotonic saline. pH at the surface was measured in the cervical, middle, and apical cavities at 0 and 3, 7, 14, 21, 28, 45, 60, 90, and 120 days. Results indicate that hydroxyl ions derived from calcium hydroxide pastes diffused through root dentin at all regions over the experimental period of 120 days. The pattern of pH change at the tooth surface was similar in all regions of the root, regardless of the type of calcium hydroxide paste used. This was a rapid rise in pH from a control value of pH 7.6, to greater than pH 9.5 by 3 days, followed by a small decline to pH 9.0 over the next 18 days, before finally rising and remaining at, or above pH 10.0 for the remainder of the experimental period. Pulpdent paste in the apical region was the only exception in this pattern, producing a pH rise nearly one full unit below the other pastes, pH 9.3. These results indicate that, for all pastes tested, a high pH is maintained at the root surface for at least 120 days. Copyright © 1996 by The American Association of Endodontists.
Keywords: calcium hydroxide; camphor; camphorated parachlorophenol; chlorophenol; hydroxyl radical; root canal filling material; analysis of variance; chemistry; dentin; diffusion; drug combination; drug effect; human; metabolism; pH; tooth cervix; tooth permeability; tooth root; Analysis of Variance; Calcium Hydroxide; Camphor; Chlorophenols; Dentin; Dentin Permeability; Diffusion; Drug Combinations; Humans; Hydrogen-Ion Concentration; Hydroxyl Radical; Root Canal Filling Materials; Tooth Cervix; Tooth Root